Motor performance and nutritional status in students with attention deficit hiperactivity disorder - do Nascimento E.M.F. (2013)
Objective: This Study aimed to characterize the motor development and nutritional status of scholars with ADHD indicative. Methods: Eighty scholars of both sexes, aged 12,30 ±1,16 years old participated; separated in groups with (n = 40) and without ADHD indicative. To identify ADHD and Motor Development were used respectively, the Hyperactivity and Attention Deficit Evaluation Scale, and the motor battery MABC-2. Height and weight were measured to calculate Body Mass Index. Data were analyzed on SPSS17 software, adopting p < 0,05 significance levels. Results: The subjects presented, in most, a normal motor development. The ADHD group showed most numbers of subjects with a "defined motor problem". It was found a statistically difference on throwing and catching skills (p = 0,005), balance (p = 0,010) and general motor development (p = 0,014) which without ADHD group presents better performance. It wasn't found any significative association between motor development and ADHD presence. The scholars showed adequate nutritional state for age, but didn't present a statistically significative difference between groups. Besides that, many subjects in both groups were classificated as overweight. An inverse relation between nutritional status and balance was found on with ADHD group (r = -0,321). Conclusions: There was difference in balance skills and abilities manuals, with poorer motor performance presented by the group with ADHD. They also found that the higher the BMI of children with ADHD worse performance in the balance.